Characteristics of Plural Phrase Formation in Al-Mu'jam Al-?ag?r Lijum?' Al-Taks?r Dictionary and Their Absorption in Learning Arabic at a Language Course - Wahyu Hanafi Putra; R. Umi Baroroh; Syamsul Hadi; Thamir Thamir As-Saady; Kunti Nadiyah Salma (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
This study aims to analyze the characteristics of the formation of plural phrases in the irregular plural noun dictionary Al-Mu'jam al-?ag?r lijum?' al-Taks?r by M. Muslikhin and identify their absorption patterns for learning Arabic at the Al-Azhar Language Course Institute, Pare Kediri. This qualitative research was done with two approaches: library research and case studies. Data sources were obtained from the dictionary and Arabic language course activities at the Al-Azhar Pare Kediri Language Course Institute. Data collection techniques were conducted by documentation and observation, and data analysis techniques were done by using data reduction, data presentation, and conclusion. The results showed that the compilation of the irregular plural noun dictionary of Al-Mu'jam al-?ag?r lijum?' al-Taks?r by M. Muslikhin has positive-pragmatic value in the development of Arabic lexicography and learning Arabic in Indonesia. Dictionaries that form particular phrases into plural phrases follow the pattern of wazan jam'u al-qillah wa jam'u al-ka?rah. Some mu??ala??t in the dictionary is formed constructively (musytaq) and permanently (j?mid). Dictionaries are arranged in alphabetical order and are thematic. It is very appropriate to help with Arabic language course activities with various programs available at LKB Al-Azhar Pare Kediri and external institutions. The theoretical implication of this research is to develop Arabic lexicographic discourse in Indonesia. Meanwhile, the practical implication is to make it easier to search for Shighat Jama' Taksir on verbs in the dictionary.